Can Situational Action Theory Explain the Gender Gap in Adolescent Shoplifting? Results From Austria. (September 2017) - Hirtenlehner, Helmut; Treiber, Kyle
Although shoplifting is one of the crimes with the smallest gender gap among all offense types, most studies still conclude that males steal from shops more frequently than females. The roots of the gendered distribution of shoplifting have not yet been satisfactorily explained. This work investigates whether situational action theory (SAT) can account for males' greater involvement in shoplifting compared to females and if the propensity–exposure interaction that is at the heart of the theory applies to both genders. Results from a large-scale student survey conducted in Austria suggest that SAT generalizes to both genders and that it is well suited to explain why males are more likely to shoplift than females.